2003
DOI: 10.1093/oxfordjournals.molbev.a004233
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive Adaptive Evolution in Mammalian Fertilization Proteins

Abstract: Mammalian fertilization exhibits species specificity, and the proteins mediating sperm-egg interactions evolve rapidly between species. In this study, we demonstrate that the evolution of seven genes involved in mammalian fertilization is promoted by positive Darwinian selection by using likelihood ratio tests (LRTs). Several of these proteins are sperm proteins that have been implicated in binding the mammalian egg coat zona pellucida glycoproteins, which were shown previously to be subjected to positive sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
406
2
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 441 publications
(430 citation statements)
references
References 18 publications
19
406
2
3
Order By: Relevance
“…Human ZP1 and ZP4 are paralogues that may have arisen from a common ancestral gene either by gene duplication or exon swapping. 11,78,79 The aa sequence identity of human ZP1 and ZP4 is 47%, which further supports the notion that AR induction mediated by ZP1/ZP4 is likely to follow similar downstream signalling events. Murine models Chemically deglycosylated forms of mouse ZP3 fail to induce the AR, suggesting that glycosylation of ZP3 is critical for its functional activity.…”
Section: Zp4supporting
confidence: 72%
See 1 more Smart Citation
“…Human ZP1 and ZP4 are paralogues that may have arisen from a common ancestral gene either by gene duplication or exon swapping. 11,78,79 The aa sequence identity of human ZP1 and ZP4 is 47%, which further supports the notion that AR induction mediated by ZP1/ZP4 is likely to follow similar downstream signalling events. Murine models Chemically deglycosylated forms of mouse ZP3 fail to induce the AR, suggesting that glycosylation of ZP3 is critical for its functional activity.…”
Section: Zp4supporting
confidence: 72%
“…77 The region of ZP3 encoded by exon 7 has undergone a relatively large number of changes during evolution compared with the remainder of the polypeptide and is a proposed site of positive Darwinian selection. 78,79 Human ZP3 has a polypeptide backbone of 424 aa, with a signal peptide (SP) at 1-22 aa that facilitates its secretion (Figure 2a). A tetra basic consensus furin cleavage site (349-352 aa) is present upstream of a hydrophobic transmembrane-like domain (387-409 aa).…”
Section: Zp3mentioning
confidence: 99%
“…4,22,23 Positive selection is pervasive among mammalian reproductive proteins, especially several sperm proteins that have been implicated in binding the egg promoting fertilization. 24 The rapid evolution of reproductive proteins may be driven by the selective forces of sperm competition, sexual selection and sexual conflict, individually, or in combination. 20 Previously, we identified the novel epididymal spermbinding protein DEFB118 25 and recently showed that DEFB118 has potent antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…LRTs were used to compare models that assume no positive selection (u < 1) with those that assume positive selection (u > 1). The seven codon substitution models are: M0 (one-ratio), M1a [34] and M8a (b þ u ¼ 1) [51]. The M1a model estimates a single parameter p 0 , the frequency of conserved sites with u 0 ¼ 0 and the remaining sites with frequency p 1 (p 1 ¼ 1 À p 0 ) assuming u 1 ¼ 1.…”
mentioning
confidence: 99%
“…The fourth comparison was between a model of beta-distributed selective pressures, that allows for 10 site classes, each with u < 1 and M8, which has 11 site classes, one of them allowed for u > 1. The last comparison was between M8 and M8a, in which an additional parameter was constrained to have u ¼ 1 [51]. In all LRTs good evidence for positive selection is found if the LRT indicates that models that allow for selection (i.e.…”
mentioning
confidence: 99%